Feedback from incident reporting: information and action to improve patient safety. Issue 1 (9th February 2009) - Benn, J; Koutantji, M; Wallace, L; Spurgeon, P; Rejman, M; Healey, A; Vincent, C
Abstract : Introduction: Effective feedback from incident reporting systems in healthcare is essential if organisations are to learn from failures in the delivery of care. Despite the wide-scale development and implementation of incident reporting in healthcare, studies in the UK suggest that information concerning system vulnerabilities could be better applied to improve operational safety within organisations. In this article, the findings and implications of research to identify forms of effective feedback from incident reporting are discussed, to promote best practices in this area. Methods: The research comprised a mixed methods review to investigate mechanisms of effective feedback for healthcare, drawing upon experience within established reporting programmes in high-risk industry and transport domains. Systematic searches of published literature were undertaken, and 23 case studies describing incident reporting programmes with feedback were identified for analysis from the international healthcare literature. Semistructured interviews were undertaken with 19 subject matter experts across a range of domains, including: civil aviation, maritime, energy, rail, offshore production and healthcare. Results: In analysis, qualitative information from several sources was synthesised into practical requirements for developing effective feedback in healthcare. Both action and information feedback mechanisms were identified, serving safety awareness, improvement and motivational functions. The provision of actionable feedback that visibly improved systems was highlighted as important in promoting future reporting. Fifteen requirements for the design of effective feedback systems were identified, concerning: the role of leadership, the credibility and content of information, effective dissemination channels, the capacity for rapid action and the need for feedback at all levels of the organisation, among others. Above all, the safety-feedback cycle must be closed by ensuring that reporting, analysis and investigation result in timely corrective actions that effectively address vulnerabilities in existing work systems. Conclusions: Limited research evidence exists concerning the issue of effective forms of safety feedback within healthcare. Much valuable operational knowledge resides in safety management communities within high-risk industries. Multiple means of feeding back recommended actions and safety information may be usefully employed to promote safety awareness, improve clinical processes and promote future reporting. Further work is needed to establish best practices for feedback systems in healthcare that effectively close the safety loop.